ANALISIS PERMINTAAN BERAS DI KOTA BENGKULU (Rice Demand in Bengkulu City) - Sarina; Saraina (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Rice is a staple food source and a strategic commodity because it can influence all policies in our country. This research aims to find out what factors influence the demand for rice in the city of Bengkulu. The research was conducted in November 2023 in Bengkulu City, Bengkulu Province. The selection of research locations was carried out with the consideration that the demand per capita for rice in Bengkulu City was higher than in other cities/regencies within the province, so it was necessary to know the factors that influenced the demand for rice in Bengkulu City. The research method uses multiple linear regression analysis. The results simultaneously have a significant effect and show that the population partially has a positive and significant effect on the demand for rice in the city of Bengkulu.